2015
DOI: 10.3109/02688697.2015.1016892
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in survivors of surgery for severe traumatic brain injury: Incidence, risk factors, and outcome from a tertiary neuroscience center in India

Abstract: Reversible AKI without need for RRT occurred in nearly 12% of patients with severe TBI requiring surgical intervention. Aminoglycoside therapy was the only predictive factor for the occurrence of AKI. Patients with AKI have a longer period of mechanical ventilation, longer ICU and hospital stay, and poorer GCS at discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…to 40%. [5][6][7]19,20 The incidence of AKI was 20.44% in our study. This difference may be caused by the different diagnostic criteria of AKI over the years and respective medical level in different hospitals.…”
Section: Discussionsupporting
confidence: 45%
“…to 40%. [5][6][7]19,20 The incidence of AKI was 20.44% in our study. This difference may be caused by the different diagnostic criteria of AKI over the years and respective medical level in different hospitals.…”
Section: Discussionsupporting
confidence: 45%
“…The incidence of AKI in our study is similar to those reported among several non-cardiac surgery cohorts, which varied from 7.5% to 24% 2, 5, 12, 13 , but lower than those in cardiac surgery 4, 17 . Although several studies had reported the incidence of AKI in traumatic brain injury cohorts, ranging from 8% to 25% 1821 , the postoperative AKI incidence of entire neurosurgical critically ill cohort has not been well described. Our investigation provided more evidences regarding incidence of postoperative AKI in such specific population.…”
Section: Discussionmentioning
confidence: 99%
“…However, physiologically body constantly excrete sodium after brain cells death due to sodium waste mechanism of the brain, which called sodium-wasting mechanism of brain. 8 Authors made this paper by following the guideline from PRISMA and Cochrane. 9,10 Higgins et al, said AKI occurrence was not a rare finding in stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Atherosclerosis, arterial hypertension, and diebetes mellitus whereas risk factors of cerebrovascular accident are common predisposing condition to create AKI. 8 Regarding the data spreaded, there were still minimal observation and the accumulative reports of CVA progress to AKI. Therefore, the objective of this metaanalysis was to evaluate the renal impairment following ischemic cerebrovascular accident (CVA) patients worldwide in order to comprehensively acknowledge prevalence of AKI following stroke and the clinical consequences on morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%